Unknown g (x) = ax + b and g (g (x)) = 16x - 15. Calculate the value of a and b.

Answers

Answer 1
Answer: g(g(x))=16x-15
means that when you subsituted g(x) for x in g(x), you got 16x-15

a(ax+b)+b=16x-15
distribute
xa^2+ab+b=16x-15d
we look at the x terms
therefor
xa^2=16x
a^2=16
a=-4 or 4
we will find out


look a constant terms
ab+b=-15
undistribute b
b(a+1)=-15

if a is -4 then
b(-4+1)=-15
b(-3)=-15
b=5

if a=4 then
b(4+1)=-15
b(5)=-15
b=-3


so
g(x)=-4x+5 or
g(x)=4x-3

if a=-4, b=5
if a=4, b=-3

Related Questions

A company made a profit of $25,000 over a period of 5 years on an initial investment of $10,000. What is its annualized ROI?
if Justin is 2 years older than ethan and in 9 years the sum of their ages will be 38 how old are they now? Can someone please help me with this question
Convert to a percentage. .35 A.3.5% B. .035% C. .35% D. 35%
Select the interval where h(x)>0 {where h of x is greater than 0}Option1. -3.5 Option2. -2 Option3. 2.5
Jack, Jo and Jim were ship wrecked on an island with monkeys and a crate of 185 bananas jack ate 5 more then Jim jo ate 3 more bananas and the monkey ate 6 bananas how many bananas did each sailor eat?

1. You have a 4 quart bottle of 70% pure apple juice. You want to mix it with 90% pure apple juiceto obtain 85% pure apple juice. How much of the 90% pure apple juice should you use?

Answers

Answer:

12 quarts of the 90% pure apple juice should be used

Step-by-step explanation:

Here, we want to calculate the number of quarts of the 90% pure apple juice to be used.

Let the number of quarts of the 90% pure apple juice to be used be x;

This brings the total of the 85% result to (4 + x)

By mathematical convention;

4 quarts of 70% + x quarts of 90% = (4 + x) of 85%

70% = 70/100 = 0.7

90% = 90/100 = 0.9

85% = 85/100 = 0.85

Thus, mathematically;

(0.7 * 4) + (0.9 * x) = 0.85(4 + x)

2.8 + 0.9x = 3.4 + 0.85x

Let’s collect like terms

3.4 -2.8 = 0.9x -0.85x

0.6 = 0.05x

x = 0.6/0.05

x = 12

Final answer:

To get an 85% pure mixture, you need to combine 4 quarts of 70% pure apple juice with 4 quarts of 90% pure apple juice. This is obtained by setting and solving an algebraic equation based on percentage purity and volume.

Explanation:

This problem relates to an area of mathematics known as algebra. We are trying to find the amount of 90% pure apple juice needed to achieve an 85% pure mixture with a 4 quart bottle of 70% pure apple juice.

First, let's set up an equation based on the given information:

70%(amount of 70% pure apple juice) + 90%(amount of 90% pure apple juice) = 85%(total amount of apple juice mix)

Since the 70% pure apple juice is 4 quarts, the equation becomes:70%(4 quarts) + 90%(x) = 85%(4 quarts + x)

Next, we will solve for x. To do this, convert the percentages into decimals, multiply through, simplify and solve.

0.7(4) + 0.9x = 0.85(4+x)  

2.8 + 0.9x = 3.4 + 0.85x

Solving for x, we get that x = 4 quarts.

So, you would need 4 quarts of the 90% pure apple juice to get an 85% pure mixture with your 4 quart of 70% pure apple juice.

Learn more about algebra here:

brainly.com/question/32436021

#SPJ3

In the figure below, hln. Find the values of z and y.

Answers

To find y:

3y-14=180

3y=194

y=64.7

To find z:

180 - 64.7 = z

z = 115.3

93 is decreased to 90

Answers

93-3=90
I hope this helps;)

Susie mows a rectangular yard with a area of 72 square meters.The yard is 6 meters wide.What is the perimeter of the yard Susie mows

Answers

You already know that the width of the yard is 6 and the area is 72. The area is the length times the width. So the length*6=72.
Divide by 6 on each side and you get the length to be 12 yards. 
Now to find the perimeter you find the sum of two times the width and two times the length. 
2(6)+2(12)=perimeter
12+24+36
So the perimeter is 36 yards. Hope this helps. 

The sum of the first and third of three consecutive even integers is 154. Find the three even integers.

Answers

x + (x+2) = 154
combine like terms
2x + 2 = 154
subtract 2
2x = 154
divide by 2
x = 76

so the two numbers are 76 and 78

16x=10(x+1)=26(+1)-16

Answers

The solution to the first pair of equal expressions is:

16x = 10(x + 1)

16x = 10x + 10

6x = 10

x = 10/6 = 1 and 2/3


The solution to the second pair of equal expressions is:

10(x + 1) = 26(+1) - 16

The left side is 10(x + 1) = 10x + 10

The right side is  26(+1) - 16 = 26-16 = 10

The equation now says    10x + 10 = 10

Subtract 10 from each side:   10x = 0

The solution to this pair of equal expressions is   x = 0 .

I think I understand the weird question now.  It's trying to say that
the first expression is equal to both the second and third expressions.
Let's try the first and the third:

16x = 26(+1) - 16

16x = 26 - 16

16x = 10

x = 10/16 = 5/8 = 0.625

Nope, that wasn't it.

The upshot of all my research is:  I have no idea what the question is trying to say,
therefore no clue of what the actual question is, and no direction toward an answer.